The Prospect of Rooftop Photovoltaic Development Considering Global Horizontal Irradiation Uncertainty and Government Policies: A Case of Java Island, Indonesia - Budi, Rizki Firmansyah Setya; Sarjiya, Sarjiya; Hadi, Sasongko Pramono (EconJournals, 2022)
Global horizontal irradiation (GHI) uncertainty and government policy significantly affect the economics of rooftop photovoltaic (PV) development. Unfortunately, previous studies neglect these aspects. Therefore, it is necessary to undertake the economic analysis of rooftop PV development by considering its GHI uncertainty and government policies. This research creates a model that can be used to perform analysis and assess rooftop PV development prospects by considering irradiation uncertainty and government policies. The attractiveness of rooftop PV development is indicated by the value of the levelized cost of electricity, net present value, and internal rate of return (IRR). Monte Carlo simulation models irradiation uncertainty. Java Island in Indonesia is used as a case study to show the performance of the proposed model. The research results show that the rooftop PV is not economically viable if built by the utility. Rooftop PV systems are only profitable when built by the private sector and is used for internal usage only. These rooftop PV investments provide an IRR above 14, which shows that investors with green capital funds and local investors are interested in investing. The emission reductions from a 100 m2 rooftop PV system vary from 214 to 384 tons of Carbon dioxide per year. © 2022, Econjournals. All rights reserved.